(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Mixed bacterial flora is responsible for the development of numerous abscesses, especially those resulting from systemic infection (septicemia) resulting from pathologies of the abdominal cavity or bile ducts. The number and volume of abscesses may vary, which affects the treatment method. Percutaneous drainage is effective in the treatment of solitary liver abscesses with a volume of < 5 cm3. Irregular abscesses are effectively drained using multipoint drainage. Hybrid drainage (endoscopic and percutaneous) is the method of choice in the treatment of abscesses resulting from obstruction of the bile ducts. Statistical significance for inflammatory markers was found only for C-reactive protein (CRP), since it correlated with drainage efficiency, i.e. the possibility of drainage efficiency decreased with increasing CRP values.